2016
DOI: 10.1016/j.foodchem.2016.04.081
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a dissolution test for lutein tablets and evaluation of intestinal permeability

Abstract: Lutein is a carotenoid with antioxidant activity that is present in various dosage forms. The bioavailability of carotenoid from oral dosage formulations depends on their release, dissolution and its permeability through the gastrointestinal tract. Here, a dissolution test was developed for evaluating formulations and the bioavailability was assessed. The test utilized a USP-apparatus II with rotations of 50, 75 and 100rpm in water with P80 at 1, 2 and 5% (w/v). A non-everted rat intestinal sac model was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…It was observed that the pure drug suspension gives a lower permeation coefficient in comparison to all optimized felodipine LPHNs formulations(F1-F9) because that felodipine LPHNs formulations belong to lipid base nanosystem that increases solubility and intestinal permeation also, nanoscale of these hybrid carriers provide large surface area for molecular felodipine libration and rapid absorption to the systemic circulation. [32][33][34] The analysis of variance indicates a significant(p-value <0.05) correlation between the blend of PEG laurate: polysorbate 80: propylene glycol contents, lipid content, and chitosan polymer and ex vivo intestinal permeation parameter.…”
Section: Ex-vivo Intestinal Permeation Studymentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the pure drug suspension gives a lower permeation coefficient in comparison to all optimized felodipine LPHNs formulations(F1-F9) because that felodipine LPHNs formulations belong to lipid base nanosystem that increases solubility and intestinal permeation also, nanoscale of these hybrid carriers provide large surface area for molecular felodipine libration and rapid absorption to the systemic circulation. [32][33][34] The analysis of variance indicates a significant(p-value <0.05) correlation between the blend of PEG laurate: polysorbate 80: propylene glycol contents, lipid content, and chitosan polymer and ex vivo intestinal permeation parameter.…”
Section: Ex-vivo Intestinal Permeation Studymentioning
confidence: 99%
“…Ex vivo study was achieved on fasted male sheep weighing about 16 kg using the non-everted sac method. [32][33][34] The animal slay and anatomize according to the legal method achieved in the university of Baghdad/ college of pharmacy. The small intestine was isolated and carefully removed mesentery matter and washed the small intestine by cold normal saline solution.…”
Section: Ex-vivo Intestinal Permeation Studymentioning
confidence: 99%
“…Robustness: The robustness refers to the ability of an analytical procedure to remain unaffected by small but deliberate variations in the parameters of the analytical method which indicating the reliability of the method for routine analysis. The robustness was determined by analyzing samples of (20μg/mL) under different conditions of the analytical method parameters, such as flow rate (0.9, 1 and 1.1 ml/min), injection volume (19, 20 and 21μl), mobile phase composition (methanol ratio of: 76, 77 and 78%) (21) .…”
Section: Limit Of Detection (Lod) and Limit Of Quantification (Loq)mentioning
confidence: 99%
“…The ex-vivo permeation study of DE-NLCs was carried out using non-averted gut sac method with modification (21,22) , male SD rats, weighing approximately 250-300 g, were fasted overnight with free access to water, anesthetized with ether and a longitudinal abdominal incision was made then the small intestine was removed and the mesentery was stripped manually and washed out carefully with cold normal saline solution using a syringe equipped with blunt end needle. The clean intestine was cut into 10 ± 0.2 cm long sacs having a diameter of 0.25mm.…”
Section: Ex-vivo Intestinal Permeation Studymentioning
confidence: 99%
“…issolution testing is used to measure the rate of drug release from a solid dosage form (1). Dissolution can be the rate-limiting step for drug absorption and is used to assess performance of the dosage form at different stages of product life cycle, ranging from product development to post-marketing surveillance (2).…”
mentioning
confidence: 99%